IN VITRO BIOLOGICAL PROPERTIES OF CRUDE METHANOL EXTRACT FROM MUSHROOM; FLAMMULINA VELUTIPES (GOLDEN NEEDLE MUSHROOM) - Jantrapanukorn, Bajaree; Powthong, Pannapa; Luprasong, Chitradee (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of this study were to investigate the in vitro biological effect of the methanolic crude extract received from edible mushrooms; Flammulina velutipes on anti-inflammatory, antioxidant activity, anti-lipid peroxidation (LPO), antimicrobial activity, and anticancer activity. The scientific result obtained here was possibility of developing this variety as an ingredient in health/medical food purposes as well as a functional food. Methods: In this study, the methanol crude extract of F. velutipes has been performed and in vitro pharmacological properties such as anti-inflammatory, antioxidant activity, anti-LPO, antimicrobial activity, and anticancer activity were evaluated. Results: The results revealed that anti-inflammatory activity of crude extract was very significant with 79.81±0.87% of the dose-dependent manner. Antioxidant and anti-low-density lipoprotein (LDL) peroxidation activity of the extract showed its capacity of free radical scavenging with high-level antioxidant compounds and lipid preventive effects (2, 2-diphenyl-1-picrylhydrazyl: 79.81±0.01%, total phenol: 991.10±0.01 μg gallic acid equivalents/0.1 g dry matter, H2O2: 93.27±0.05%, LPO: 33.33±0.00%, and LDL: 57±0.03%, respectively). Analysis has also demonstrated that the methanolic extract of F. velutipes provided an antimicrobial activity to ESBL-producing Klebsiella pneumoniae. Moreover, F. velutipes extract showed a growth inhibitory effect in HepG2 cells with the 50% inhibitory concentration (IC50) value IC50=8.25±7.59 μg/ml. Conclusion: This indicated that crude extract from F. velutipes was scientifically proved as a potential source of therapeutic agent and be able to utilize as a functional ingredient for healthy or supplement food.